REVITALISASI NILAI BUDAYA MELALUI PERMAINAN GALAH PANJANG DI MASYARAKAT KEPULAUAN RIAU - Yozi Rahmadeni; Doni Septian (STAIN Sultan Abdurrahman Kepulauan Riau, 2018)
Traditional games are part of cultural products in the community that also have cultural values of the community itself. This article aims to investigate the cultural values of Galah Panjang in the Riau Islands to explore the values contained. In the early study, it is known that this game is included in the type of male group game in the form of competition. So that the values contained include the value of compactness, leadership, responsibility, and work ethic. In addition, the game can stimulate psychological development for children. From this study, the revitalization of regional cultural values needs to be a reference for the development of national culture that is full of the Indonesian characters.